Digital Queueing Innovation and Outpatient Service Quality: Integrating Technology Acceptance and SERVQUAL at a Military Hospital in Indonesia - Alfina Mentari Salsabila; Suhat Suhat; Novie Elvinawaty Mauliku; Ayu Laili Rahmiyati (STIKep PPNI Jawa Barat, 2026)
Background: Long waiting times in outpatient services often reduce service quality. Digital solutions such as online queue systems, including Mobile JKN, are increasingly used to improve efficiency, but their impact on overall service quality remains unclear. Objective: This study aims to examine how effective an online queue system is in improving service quality at Dustira Hospital. Methods: A quantitative approach with a cross-sectional design was applied. Participants were selected through purposive sampling, resulting in a total of 379 respondents. Data were collected using structured questionnaires with Likert-scale responses to assess both the performance of the online queue system and perceived service quality. The independent variable refers to the effectiveness of the online queue system, evaluated using the Technology Acceptance Model (TAM), which includes perceived usefulness, perceived ease of use, behavioral intention, and actual system utilization. The dependent variable is service quality, measured through SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis consisted of univariate statistics, Chi-square testing for bivariate analysis, and logistic regression for multivariate analysis. Results: Most respondents were adults aged 18–59 years, male, and had completed secondary education. Bivariate analysis showed a significant association between online queue system effectiveness and perceived service quality (p < 0.05). In the multivariate model, perceived ease of use emerged as the only significant predictor of service quality (p < 0.05; OR = 1.874), indicating that patients who perceived the system as easier to use were more likely to report better service quality. Conclusion: The implementation of an online queue system contributes positively to service quality at Dustira Hospital. Greater ease in system usage is associated with better perceived service quality among patients.